Association of tensor fascia lata hypertrophy and fatty infiltration in the presence of abductor tendon tears: a radiographic study. Issue 2 (30th August 2021) - Quinn, Matthew; Levins, James; Mojarrad, Mohammadali; O'Donnell, Ryan; DeFroda, Steven; Haggerty, Erin; Evangelista, Peter; Tabaddor, Ramin
ABSTRACT: Hip abductor tendon tears of the gluteus medius and minimus are becoming a well-recognized source of pain and dysfunction, primarily in middle-age females. Like the rotator cuff, fatty infiltration (FI) can occur after tearing of these tendons. While the association of TFL hypertrophy after abductor tendon tears has been established, its association with FI has not been well studied. Our hypothesis is that hypertrophy of the TFL will be associated with FI of the abductors. All patients >18 years old undergoing primary surgical repair for a confirmed tears on MRI, without a history of prior hip surgery or osteoarthritis, were included. The following measurements were obtained from MRI: TFL cross-sectional area, TFL:sartorius volume ratio, and modified Goutallier grade of gluteus medius and minimus. Seventy patients met inclusion criteria and were divided in two groups, those with ( n = 28) and those without FI ( n = 42) of the abductors. The FI group was on average older (65 versus 58 years, P < 0.00016). TFL hypertrophy and TFL:sartorius volume ratio were significantly associated with FI ( P = 0.00069). Following abductor tendon tear and subsequent FI, there exists significant TFL hypertrophy in patients without a prior history of hip surgery in our patient cohort.